Effects of processing parameters on relative density, microhardness and microstructure of recycled Ti-6Al-4V from machining chips produced by equal channel angular pressing - Alex Shi; Yau Tse; Rebecca Higginson (2015)
Ti-6Al-4V was recycled from machining chips by using equal channel angular pressing (ECAP). Samples were pressed through a die up to 8 passes at moderate temperatures in the range of 400-500 °C. The ECAP process was accomplished with back-pressures ranging from 50 to 250. MPa. The results demonstrate that ECAP with back-pressures allows the consolidation of machining chips to near fully dense (~99.9%) recycled products. The relative density of the as-recycled samples increased with the applied back-pressure and number of passes. The average hardness and homogeneity were improved as the number of passes increased. The transmission electron microscopy reveals a combination of equiaxed and elongated α grains after the first pass. With subsequent pressing, the samples were dominated by nano-equiaxed α grains with diameters of ~70 nm. The original β phase in the machining chips was fragmented during the ECAP process.